CAUSES AND EFFECTS OF TECHNOSTRESS IN THE WORKPLACE: A SYSTEMATIC LITERATURE REVIEW - Bešlagić, Mirza; Đonlagić Alibegović, Sabina (Poslovna ekonomija, 2024)
ABSTRACT: Modern life circumstances have led to the fact that people spend more and more time connected to their computers. As digital technologies become present in societies, the psychological and physical effects of its use become evident in its users. The aim of the paper is to explain the creators and effects of technostress in the workplace. The paper presents an overview of the research results so far in the field of digitization of the workplace. The most significant factors of technostress that have been identified are: creators of technostress, use of technology, multitasking, uncertainty about new technologies and exposure to screens. Technostress has significant effects on work productivity, employee health, commitment to the organization and business decision-making. Literature sources include scientific papers published in various scientific databases. The limitation in this paper is the impossibility of accessing all articles dealing with the topic of technostress. The results can serve as a foundation for understanding the challenges that managers face in modern business conditions.